2018
DOI: 10.1007/s00706-018-2188-9
|View full text |Cite
|
Sign up to set email alerts
|

Umbelliferone instability during an analysis involving its extraction process

Abstract: Umbelliferone (7-hydroxycoumarin) is one of the most popular compounds of the coumarins family. This compound receives the attention of scientists due to its diverse bioactivities in a number of applications in various therapeutic fields. An interesting aspect of umbelliferone is its structural lability. The enzymatic degradation process of umbelliferone to its hydroxylated (esculetin), glucosylated (skimmin), and methylated (herniarin) derivatives is already known from the literature. In this paper, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Plant coumarins, often called phytoalexins, are believed to be compounds that help plants defend themselves when living and nonliving things cause stress [74]. The literature previously described the enzymatic breakdown of umbelliferone (COU2) to its glucosylated (skimmin (COU1)) and methylated (herniarin (COU3)) derivatives [75]. Our results support what other studies have found: higher concentrations of herniarin than umbelliferone can be extracted from chamomile flower heads [40,76].…”
Section: Discussionsupporting
confidence: 88%
“…Plant coumarins, often called phytoalexins, are believed to be compounds that help plants defend themselves when living and nonliving things cause stress [74]. The literature previously described the enzymatic breakdown of umbelliferone (COU2) to its glucosylated (skimmin (COU1)) and methylated (herniarin (COU3)) derivatives [75]. Our results support what other studies have found: higher concentrations of herniarin than umbelliferone can be extracted from chamomile flower heads [40,76].…”
Section: Discussionsupporting
confidence: 88%
“…The pH-dependent spectral properties of FLU have been already elaborated in the literature , and have been attributed to the existence of different protolytic forms of the dye and the occurrence of protolytic reactions in the excited state (Scheme S1). Even though some researchers have elucidated the pH-dependent spectral properties of UMB , , there is a lack of literature studies explaining the relation between its fluorescence behavior and the corresponding structural changes vis-a-vis pH variation.…”
Section: Resultsmentioning
confidence: 99%
“…Organic solvents are mostly used in extraction of coumarins from different matrices; however, extraction methods operating at higher temperatures, pressures, or with energy field assistance offer some advantages such as lower organic solvent consumption and shorter extraction time (Rodríguez-García and Raghavan, 2022) 1). However, such high temperatures may cause the decomposition of thermolabile components and extraction of undesirable impurities (e.g., umbelliferone is chemically and thermally unstable, which may result in many compounds formed during its reflux extraction by methanol, ethanol, buffers, and buffered or non-buffered alcohol/water mixtures (Dawidowicz et al, 2018)). Extraction efficiency depends also on the extraction time and mostly increases with the increased extraction time in a certain time interval.…”
Section: Optimisation Of the Solvent Extraction Proceduresmentioning
confidence: 99%